(untitled) (Global Journal of Science Frontier Research, 2020)
It is shown in the paper that forced heat transfer exchange during quenching silver probes in cold electrolytes is explained by periodical replacement of short film boiling process by shock boiling. The frequency of such process is very high that increases cardinally heat transfer exchange. This phenomenon doesn’t fit contemporary theory concerning nucleate boiling processes and needs further careful investigations. The reason for existing periodical process is a double boundary electrical layer where are acting increased electrical forces during quenching in electrolytes. In contrast of quenching steel, silver generates higher heat flux density during quenching; however full film boiling cannot be developed due to presence of high electrical forces in a double electrical layer caused by increased electrical conductivity of silver. The discovered phenomenon can be used in the practice in the future after its careful investigation to force heat transfer exchange by external electrical forces to eliminate any film boiling process during batch quenching.